Hypertension and Aortic Stenosis: A Review - Rassa, Allen; Zahr, Firas (Current Hypertension Reviews, 2018)
Background: Aortic stenosis is a common form of valvular heart disease which often coexists with hypertension. These diseases represent two distinct forms of left ventricular systolic overload and in combination may be associated with disadvantageous left ventricular remodeling, increased mortality and heart failure. The treatment of hypertension in aortic stenosis remains a challenging problem with limited data to guide clinical practice. Methods: We performed a comprehensive online literature review to find relevant published literature on the topic of hypertension and aortic stenosis. Results: In the present manuscript, we review the pathophysiology of aortic stenosis in combination with hypertension and the effects on the left ventricle. We also provide general recommendations for medical therapy for treatment of hypertension in aortic stenosis and review the available data on specific antihypertensive agents in this context. Conclusions: Aortic stenosis and hypertension commonly coexist and significantly impact the diagnosis and classification of aortic stenosis severity and symptoms. Treatment of hypertension among patients with severe aortic stenosis can be challenging. Among specific antihypertensive agents studied in this context, ACE-inhibitors are the most well studied.
Keywords: hypertension